Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to find the expression for the following series. It is similar to a geometric series but I don't get how to find the answer.



share|cite|improve this question
It is a geometric series: the first term is $b$, the last term is $a^{n-1}b^n$, and the ratio is $ab$. – Brian M. Scott Apr 9 '12 at 7:31

1 Answer 1

up vote 1 down vote accepted

You have

$$ \sum_{i=1}^n a^{i-1} b^i = b \left ( \sum_{i=1}^n a^{i-1} b^{i-1} \right ) $$

Now compute

$$\sum_{i=1}^n a^{i-1} b^{i-1} = \sum_{i=0}^{n-1} a^{i} b^{i} = \sum_{i=0}^{n-1} (ab)^{i} = \sum_{i=0}^{n-1} q^{i}$$

Hope this helps.

share|cite|improve this answer
this solved my issue, thanks. – RushK Apr 9 '12 at 8:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.